Processing of Green waste for production of compost - Siti Nurbaidzuri, Binti Reli @ Raily (Universiti Malaysia Sarawak (UNIMAS), 2013)
The use of compost in plantation is very important as an amendment to the soil. This study was not only significant in reducing the amount of waste in landfills but also helps the city to process their green wastes and to produce their own compost for landscape activities. It is essential to encourage composting by transforming any potential green wastes to become a usable and high quality end product. Aeration, temperature and moisture content are three imponant principals which control the composting proces . A total of 365 kg of green waste was used as materials for composting and towards the end of the process the weight was reduced by 160.4 kg. This study foc uses on the process of green wastes to produce compost and explores the suitable type of material used. The m thod used was box composting due to its simple operation, with manual turning once a week. Three types of compost namely Compost A, Compost B and Compost C was produced from different types of green wastes. Green wastes used for compost A were fruits, vegetables, green leaves, grasses and compost materials from DBKU c mpost centre that has undergo decomposition for about two months. Hence. compost A was only used as the baseline in this study. Compost B consisted of grasses, leaves, vegetables and fruits. Compost C was a mixture of grasses and leaves from garden trimming. The initial weight of fresh Compost Band C was 87.9 kg and 56.4 kg and the weight loss after 30 days of composting was 52.2 kg (59.4%) and 26.6 kg (52.5%), respectively. The weight of the final marketable product from Compost B was 35.7 kg and Compost C at 26.8 kg. From the re ult of this study, the best compost was compost C (C/N ratio 12:1, weight reduction of 52.5%) which gave the highest Germination Index at 171 % (Green bean seeds test), germinated in 20% compost concentration.